Modulation of Visual Responses by Gaze Direction in Human Visual Cortex - Merriam, Elisha P. (Society for Neuroscience, 2013)
To locate visual objects, the brain combines information about retinal location and direction of gaze. Studies in monkeys have demonstrated that eye position modulates the gain of visual signals with “gain fields,” so that single neurons represent both retinotopic location and eye position. We wished to know whether eye position and retinotopic stimulus location are both represented in human visual cortex. Using functional magnetic resonance imaging, we measured separately for each of several different gaze positions cortical responses to stimuli that varied periodically in retinal locus. Visually evoked responses were periodic following the periodic retinotopic stimulation. Only the response amplitudes depended on eye position; response phases were indistinguishable across eye positions. We used multivoxel pattern analysis to decode eye position from the spatial pattern of response amplitudes. The decoder reliably discriminated eye position in five of the early visual cortical areas by taking advantage of a spatially heterogeneous eye position-dependent modulation of cortical activity. We conclude that responses in retinotopically organized visual cortical areas are modulated by gain fields qualitatively similar to those previously observed neurophysiologically.